2016
DOI: 10.1007/s11916-016-0545-0
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin: Pharmacology and Therapeutic Roles in Pain States

Abstract: Botulinum toxin, also known as Botox, is produced by Clostridium botulinum, a gram-positive anaerobic bacterium, and botulinum toxin injections are among the most commonly practiced cosmetic procedures in the USA. Although botulinum toxin is typically associated with cosmetic procedures, it can be used to treat a variety of other conditions, including pain. Botulinum toxin blocks the release of acetylcholine from nerve endings to paralyze muscles and to decrease the pain response. Botulinum toxin has a long du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 32 publications
1
34
0
4
Order By: Relevance
“…Meanwhile, it had the similar function mode to the other three kinds of toxins whose effect duration was ~3 months. Consistent with previous studies, our present study also confirmed the strongest effect of toxins 1 week postinjection and the gradual recovery of muscle function to base level after injection for 12 weeks 19,31. This was in line with clinical data that effective duration of BoNT/A would range from ~3 to 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, it had the similar function mode to the other three kinds of toxins whose effect duration was ~3 months. Consistent with previous studies, our present study also confirmed the strongest effect of toxins 1 week postinjection and the gradual recovery of muscle function to base level after injection for 12 weeks 19,31. This was in line with clinical data that effective duration of BoNT/A would range from ~3 to 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…Even if more than 10,000 lethal doses of unmodified toxin tested, it was evoked a striking response-protection against subsequent challenge against C. botulinum infection (Mohanty et al, 2001). Moreover, botulinum toxin derivatives (Botox®, Botox Cosmetic®, Dysport® and Xeomin®) are approved as commercial therapeutic and cosmetic preparations by the United States Food and Drug Administration (Guaita and Hogl, 2016;Patil et al, 2016;Sundaram et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In spasticity, Botulinum Toxin is used to reduce muscle hyperactivity by blockade of the pre-synaptic terminal to prevent acetylcholine release [6]. In pain management, Botulinum Toxin has been shown to inhibit nociceptive neurotransmitters such as substance P, glutamate and Calcitonin Gene-Related Peptide (CRGP) [7]. However evidence has shown that following treatment with Botulinum Toxin for neuropathic pain, there were no changes in total concentrations of substance P or CGRP in biopsy samples.…”
Section: Discussionmentioning
confidence: 99%